2019
DOI: 10.1002/phar.2260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Safety Outcomes Following Uncontrolled Tacrolimus Conversion in Adult Transplant Recipients

Abstract: PURPOSE To compare clinical and safety outcomes of transplant recipients converted between different tacrolimus formulations to those patients who remained on a single formulation in an outpatient environment. METHODOLOGY This was a single-center, retrospective cohort study at a large tertiary care medical center with an associated institutional outpatient pharmacy system. Adult transplant recipients with institutional pharmacy refill from August 1, 2009, to May 31, 2016, were assessed. Patients were allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, drug homogeneity in the generic group may be suspicious. In Lichvar's study (21), there were no differences in renal functions, acute rejection and hospitalization episodes between the groups of original tacrolimus (Prograf®, group 1), generic tacrolimus (Tacrolimus-Sandoz®, group 2), change from original to generic (group 3), change from generic to generic (group 4). In Liu's study (22), it was reported that generic tacrolimus was widely accepted in the USA, with a % 90 market share in some states.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, drug homogeneity in the generic group may be suspicious. In Lichvar's study (21), there were no differences in renal functions, acute rejection and hospitalization episodes between the groups of original tacrolimus (Prograf®, group 1), generic tacrolimus (Tacrolimus-Sandoz®, group 2), change from original to generic (group 3), change from generic to generic (group 4). In Liu's study (22), it was reported that generic tacrolimus was widely accepted in the USA, with a % 90 market share in some states.…”
Section: Discussionmentioning
confidence: 85%